Morphometric And Phylogenetic Analysis of Goby Fish (Glossogobyus giuris) In The Three Integrated Lakes On South Sulawesi, Indonesia. - Hadiratul KUDSIAH, ,- (Romanian Inventors Forum, 2022)
The white goby fish, Glossogobius giuris is a germplasm in Tempe Lake that is decreasing due to the genetic barrier. This becomes a threat for its population in the three integrated lakes, namely Sidenreng, Lapompakka, and Tempe. Hence, efforts are needed to preserve its population and habitat by conservation programs to prevent the extinction of this fish. This conservation program is carried out when the basic biology information and population structure of goby fish are known. Therefore, this study aims to analyze the genetic variation of goby fish through morphometric and phylogenetic analysis in the three integrated lakes. The morphometric analysis was carried out using Stepwise Discriminant Analysis, while the difference in genetic distance between populations was analyzed using Predicted Group Membership and Pairwise Group Comparison, and the identifiable characters were analyzed using the Equality of Group Means Test. Similarly, the phylogenetic analysis was conducted based on mitochondrial DNA (mtDNA) targeting Cytochrome C Oxidase subunit I (COI). The morphometric analysis showed that each population has a special character with a very low value of similarity between populations. Furthermore, there were 17 and 18 identifiable characters for males and females, respectively in this study. Based on phylogenetic analysis, three groups of goby fish with low genetic diversity were identified. In addition, there was one haplotype shared by the three populations, but the other 7 haplotypes are unique, which indicated genetic speciation of goby fish from these lakes. Based on these results, goby fish from the three integrated lakes have special characters, adaptive potential, and genetic speciation due to the declining population in the lakes.